Modulation of the Inflammatory Process by Hypercholesterolemia in Osteoarthritis - Villalvilla, Amanda; Larrañaga-Vera, Ane; Lamuedra, Ana; Pérez-Baos, Sandra; López-Reyes, Alberto G.; Herrero-Beaumont, Gabriel; Largo, Raquel (Frontiers in Medicine, 2020)
Objective: Several studies have linked metabolic syndrome to the development of osteoarthritis (OA) through hypercholesterolemia, one of its components. However, epidemiological studies showed contradictory results, and it is not clear how hypercholesterolemia itself, or oxidized LDL (oxLDL) —a pathological molecule potentially involved in this relationship― could be affecting OA. The objectives of this study were to investigate the effect of hypercholesterolemia induced by high-fat diet (HFD) in cartilage from OA rabbits, and how oxLDL affect human chondrocyte inflammatory and catabolic responses. Design: New Zealand rabbits were fed with HFD for 18 weeks. On week 6, OA was surgically induced. At the end of the study, cartilage damage and IL-1β, IL-6, MCP-1, MMP-13 and COX-2 expression in articular cartilage were evaluated. In addition, cultured human OA articular chondrocytes were treated with oxLDL at concentrations equivalent to those expected in synovial fluid from HFD rabbits, in the presence of IL-1β and TNFα. The effect of oxLDL on cell viability, nitric oxide production and catabolic and pro-inflammatory gene expression was evaluated. Results: HFD intake did not modify cartilage structure or pro-inflammatory and catabolic gene expression and protein presence, both in healthy and OA animals. OxLDL did not affect human chondrocyte viability, ADAMTS5 and liver X receptor (LXR) α gene expression, but decreased the induction of IL-1β, IL-6, MCP-1, MMP-13, iNOS and COX-2 gene expression and MMP-13 and COX-2 protein presence, evoked by cytokines. Conclusions: Our data suggest that cholesterol intake per se may not be deleterious for articular cartilage. Instead, cholesterol de novo synthesis and altered cholesterol metabolism could be involved in the associations observed in human disease.